Soluble suppression of tumorigenicity 2 associated with left ventricular thrombosis in patients with ST-segment elevation myocardial infarction - Xinjia Du; Perkash Kumar; Chen Liu; Jiahua Liu; Lei Chen; Yuan Lu; Zhuoqi Zhang (BMC Cardiovascular Disorders)
Abstract Background Left ventricular thrombosis (LVT) after acute ST-segment elevation myocardial infarction (STEMI) is closely related to inflammation. Soluble Suppression of Tumorigenicity 2 (sST2) expressed as a novel inflammatory marker, has received much attention in recent years. However, the relationship between sST2 and LVT is unclear. This study aimed to investigate the correlation between sST2 and LVT formation after emergency PCI (pPCI) in STEMI patients. Methods 293 patients with STEMI who were tested for sST2 at admission within 24 h at the Affiliated Hospital of Xuzhou Medical University from June 2018 to August 2023 were consecutively enrolled and evaluated for myocardial infarction characteristics and the presence of LVT by cardiac magnetic resonance imaging (CMR). The diagnosis of LVT was defined as a left ventricular cavity in the late gadolinium enhancement (LGE) of CMR with a low signal intensity mass. Results A total of 38 patients developed LVT after STEMI, multivariable logistic regression analysis showed that sST2 [P = 0.002, OR = 1.01 (1.01 ~ 1.02)] an independent predictor of LVT formation. The results of the net reclassification index (NRI) and Integrated Discrimination Improvement Index (IDI) suggested that sST2 could improve the conventional model of LVT. A linear relationship between sST2 and LVT was fitted using a restricted cubic spline (RCS). Conclusion sST2 was independently associated with LVT formation after pPCI in STEMI patients, and sST2 improved the risk modeling of LVT. Clinical trial number Not applicable.